The adverse impact of a gain in chromosome 1q on the prognosis of multiple myeloma treated with bortezomib-based regimens: A retrospective single-center study in China - Chen, Qingxiao; Han, Xiaoyan; Zheng, Gaofeng; Yang, Yang; Li, Yi; Zhang, Enfan; Yang, Li; Dong, Mengmeng; He, Donghua; He, Jingsong; Cai, Zhen (Frontiers in Oncology, 2022)
Background: Multiple myeloma is genetically heterogeneous, and chromosome abnormalities play a pivotal role in prognosis. A gain in chromosome 1q (+1q) is among the most common cytogenetic abnormalities; however, its relationship with overall survival (OS) and progression-free survival (PFS) in patients with multiple myeloma is still unclear. We aim to clarify the impact of +1q on the clinical characteristics and survival outcomes of patients treated with bortezomib-based combination regimes. Materials and methods: We retrospectively analyzed 258 patients first diagnosed with myeloma who underwent bortezomib-based therapy at the bone marrow transplantation department of a multiple myeloma treatment center in the first affiliated hospital of Zhejiang University, China. Results: We identified 258 newly diagnosed patients with multiple myeloma in our department from July 2013 to September 2018. We observed that 127 (49.2%) of the patients acquired +1q at diagnosis, and +1q strongly correlated with the occurrence of del(13q) and IgH rearrangement (P < 0.001). In the patients with +1q, the PFS was 22.2 months (95% CI 15.8–28.5 months), and the three-year and five-year PFS was 35.1% and 15.3%, respectively. Univariate analysis revealed that albumin, lactate dehydrogenase (LDH), and the percentage of plasma cells significantly affected PFS. Multivariate analysis showed that LDH and the percentage of plasma cells significantly affected PFS in the +1q patients. In terms of OS, the median OS for the +1q patients was 47.4 months (95% CI 34.7–59.5), while the OS of the non-+1q patients was not reached (P = 0.048). The univariate and multivariate analyses revealed that age, platelet count, and extramedullary lesions were significant adverse factors for OS in the +1q patients. There were no statistical differences between PFS and OS when there were other chromosomal abnormalities, but there was a decreased tendency in PFS. LDH and +1q also had a synergistic adverse effect on survival. Conclusion: +1q is associated with a higher tumor burden and correlated with the occurrence of del(13q) and IgH rearrangement at diagnosis. In the era of novel agents, +1q still significantly affects PFS and OS.